PERANCANGAN SISTEM INFORMASI PSIKOTEST ONLINE DALAM SELEKSI DAN REKRUTMEN KARYAWAN MENGGUNAKAN METODE WATERFALL BERBASIS WEB (STUDI KASUS : PT. FORTUNARACK SISTEM INDONESIA) - Latif Sugiarto (CV. Multi Kreasi Media, 2024)
Here are still many, even almost all types of companies that still use conventional methods in manually selecting and giving psychological tests to prospective employees, one of which is PT. Fortunarack Sistem Indonesia which is still selecting and giving psychological tests to prospective employees manually. Create an online psychological test information system in computerized recruitment and selection. The making of this application uses the programming language PHP and MySql for the database.Keywords: Psychotest Online; PT. Fortunerack Indonesian System; PHP; MySql.